In Vitro Study of Fracture Load and Fracture Pattern of Ceramic Crowns: A Finite Element and Fractography Analysis - Campos, Roberto Elias; Soares, Carlos Jose; Quagliatto, Paulo S.; Soares, Paulo Vinicius; Oliveira Junior, Osmir Batista de [UNESP]; Freitas Santos-Filho, Paulo Cesar; Salazar-Marocho, Susana M. (Wiley-Blackwell, 2011)
Purpose: This in vitro study investigated the null hypothesis that metal-free crowns induce fracture loads and mechanical behavior similar to metal ceramic systems and to study the fracture pattern of ceramic crowns under compressive loads using finite element and fractography analyses.Materials and Methods: Six groups (n = 8) with crowns from different systems were compared: conventional metal ceramic (Noritake) (CMC); modified metal ceramic (Noritake) (MMC); lithium disilicate-reinforced ceramic (IPS Empress II) (EMP); leucite-reinforced ceramic (Cergogold) (CERG); leucite fluoride-apatite reinforced ceramic (IPS d.Sign) (SIGN); and polymer crowns (Targis) (TARG). Standardized crown preparations were performed on bovine roots containing NiCr metal dowels and resin cores. Crowns were fabricated using the ceramics listed, cemented with dual-cure resin cement, and submitted to compressive loads in a mechanical testing machine at a 0.5-mm/min crosshead speed. Data were submitted to one-way ANOVA and Tukey tests, and fractured specimens were visually inspected under a stereomicroscope (20x) to determine the type of fracture. Maximum principal stress (MPS) distributions were calculated using finite element analysis, and fracture origin and the correlation with the fracture type were determined using fractography.Results: Mean values of fracture resistance (N) for all groups were: CMC: 1383 +/- 298 (a); MMC: 1691 +/- 236 (a); EMP: 657 +/- 153 (b); CERG: 546 +/- 149 (bc); SIGN: 443 +/- 126 (c); TARG: 749 +/- 113 (b). Statistical results showed significant differences among groups (p < 0.05) represented by different lowercase letters. Metal ceramic crowns presented fracture loads significantly higher than the others. Ceramic specimens presented high incidence of fractures involving either the core or the tooth, and all fractures of polymer crown specimens involved the tooth in a catastrophic way. Based on stress and fractographic analyses it was determined that fracture occurred from the occlusal to the cervical direction.Conclusions: Within the limitations of this study, the results indicated that the use of ceramic and polymer crowns without a core reinforcement should be carefully evaluated before clinical use due to the high incidence of failure with tooth involvement. This mainly occurred for the polymer crown group, although the fracture load was higher than normal occlusal forces. High tensile stress concentrations were found around and between the occlusal loading points. Fractographic analysis indicated fracture originating from the load point and propagating from the occlusal surface toward the cervical area, which is the opposite direction of that observed in clinical situations.
Keywords: Mechanical properties; Dental materials; Single crowns; Stress distribution; Fractography analysis